1992
DOI: 10.1177/154079699201700201
|View full text |Cite
|
Sign up to set email alerts
|

Using Self-Scheduling to Promote Self-Directed Leisure Activity in Home and Community Settings

Abstract: The effects of self-scheduling plus training to implement weekly schedules on the frequency, diversity, and novelty of self-directed leisure activities by three adults with moderate developmental disabilities living in the community wereexamined in this study. Self-scheduling consisted of the adults choosing desired leisure/recreational activities via picture cards, and then placing the cards in a sequenced activity book for each day of the week. Training for schedule implementation consisted ofa daily prompt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 7 publications
1
27
0
1
Order By: Relevance
“…The extent to which activity planning is a necessary, if insufficient, condition for increased resident engagement requires further focused research. Findings by Anderson et al (1997), Bambara and Ager (1992), and Saunders and Spradlin (1991) highlight other areas for future research, including: (a) the use of photographs and pictures to assist clients to become more directly involved in activity planning, and (b) how client choice of activities and selfdirection can be promoted in more sophisticated ways in the future.…”
Section: Consumer Participationmentioning
confidence: 94%
“…The extent to which activity planning is a necessary, if insufficient, condition for increased resident engagement requires further focused research. Findings by Anderson et al (1997), Bambara and Ager (1992), and Saunders and Spradlin (1991) highlight other areas for future research, including: (a) the use of photographs and pictures to assist clients to become more directly involved in activity planning, and (b) how client choice of activities and selfdirection can be promoted in more sophisticated ways in the future.…”
Section: Consumer Participationmentioning
confidence: 94%
“…Utilizing the visual strengths of individuals with ASD involves physical organization, schedules, work/activity system, and a variety of visual and organizational strategies for clarifying task requirements. As reviewed by Mesibov, Browder and Kirkland (2002), previous research has shown the effectiveness of using schedules to ease transitions (Dooley, Wilczenski, & Torem, 2001;Flannery & Horner, 1994), to increase independence in task performance (Anderson, Sherman, Sheldon, & McAdam, 1997;Pierce & Schriebman, 1994), to follow a preset work or school routine (Browder & Minarovic, 2000;Clarke, Dunlap, & Vaughn, 1999;Hall, McClannahan, & Krantz, 1995), and to increase the initiation, length, and generalization of leisure activities (Bambara & Ager, 1992;. In addition, the use of visual strategies provides predictability, thus reducing confusion and behavior problems (Clarke et aI., 1999;Dooley et aI., 2001;Flannery & Horner, 1994, Krantz et aI., 1993.…”
Section: Treatment Programsmentioning
confidence: 97%
“…The CLLC provides opportunities for the residents to acquire new leisure skills using the schedules, work systems, and visual instructions that have been demonstrated to increase variety of leisure activities and self initiation (Bambara & Ager, 1992) and to increase response chains and the generalization ofthese skills (MacDuff et aI., 1993). In addition to individualized teaching programs designed to increase these skills, the entire CLLC program has at least one evening a week specifically devoted to teaching new leisure skills.…”
Section: Leisure and Social Skill 'Andainingmentioning
confidence: 98%
“…Use of pictures provides a good form of assistance for people who have learning difficulties. Using pictorial cues, students with intellectual disabilities have been taught to prepare foods (Martin, Rusch, James, Decker, & Trytol, 1982), to learn child-care skills Feldman, 2004;Feldman, Ducharme, & Case, L. (1999), to function more independently in a job setting (Connis, 1979) or in leisure activities (Bambara & Ager, 1992), to initiate and maintain grooming behaviours (Thinesen & Bryan, 1981), to develop pedestrian navigations skills (Kelley, 2012) and withdraw money and purchase items using a debit card (Alberto, Cihak, & Gama, 2005). Pictorial cues have been found to be more effective than verbal cues in promoting functional activities among children with disabilities (Caffó, Albano, Damato, & Stella, 2013;West, 2008).…”
Section: Introductionmentioning
confidence: 99%